Implementation of Marriage Registration in Aceh Qanun Number 6 of 2008 concerning Administrative Registration (Analysis of Illegal Marriage Practices in Lhoksukon District, North Aceh Regency) - Teuku Islahuddin; Dhiauddin Tanjung; Ramadhan Syahmedi Siregar (Britain International for Academic Research (BIAR) Publisher, 2022)
The implementation of Aceh Qanun Number 6 of 2008 Regarding Marriage Registration in Lhoksukon North Aceh, if analyzed based on the theory of legal effectiveness, is considered not maximally effective, even though this qanun has been enforced since 2018 and marriages carried out with wild qadhi . In addition, there are still many couples who submit Isbat Nikah to the Syar'iyah Court cannot prove their marriage at the time of examination in court. Legally, this qanun is very good. From the aspect of law enforcement, it still has weaknesses because the socialization carried out has not had a significant impact on the community, and the infrastructure is considered adequate, but from the aspect of public awareness it is still very low. Qanun Number 6 of 2008 concerning the Implementation of Population Administration relating to the registration of marriages is stated in several articles, namely Article 3, where the purpose of registering marriages is to ensure the legal status of each resident; protection of the rights of the population; ordered population administration; management of population administration information; and guarantee services for the rights of the population. Marriage registration is more firmly and specifically stated in Article 55 and Article 56. Article 55: (1) Every marriage, whether for residents who are Muslim or other religions, must be recorded. (2) Marriage registration for residents who are Muslim as referred to in paragraph (1) is carried out by marriage registrar employees at the District Religious Affairs Office. (3) The registration of marriages for residents of other religions as referred to in paragraph (1) is carried out by officials of the Regency/Municipal Population and Civil Registry Office. (4) The marriage registrar at the District Office of Religious Affairs shall record the marriage on the Marriage Certificate and issue the Marriage Certificate Quotation. (5) The Civil Registration Officer shall record marriages on the Marriage Certificate Registry and issue a Marriage Certificate Quotation. (6) Data on the results of marriage registration must be submitted by the District Office of Religious Affairs to the Regency/Municipal Population and Civil Registry Service within 10 (ten) days after the marriage registration is carried out. Article 56: Marriage registration as referred to in Article 55 also applies to: a) marriages determined by the court/Shari'ah Court; b) marriages of foreign nationals conducted in Aceh at the request of the foreign nationals concerned.